2020
DOI: 10.37043/jura.2018.10.2.5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Economic Activities and Internal Economic Integration in Romania

Abstract: This paper aims to consider two tendencies in economy simultaneously: internal integration within the country and localization of economic activities. Firstly, we examine the quantitative measurement of internal economic integration in Romania. Different methods of economic integration measuring have been developed over time, so we have defined and discussed three approaches. To estimate a level of internal integration the link between the region's share in the total output and production factors was estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…This analysis revealed that after 1990, the change of political regime and transition to an open market economy (Yaskal et al 2018) affected the economic situation in the two cities studied. The closure or reduction of production for industrial units caused economic decline and changes in the demographic situation of these cities.…”
Section: Present Economic Situationmentioning
confidence: 98%
“…This analysis revealed that after 1990, the change of political regime and transition to an open market economy (Yaskal et al 2018) affected the economic situation in the two cities studied. The closure or reduction of production for industrial units caused economic decline and changes in the demographic situation of these cities.…”
Section: Present Economic Situationmentioning
confidence: 98%
“…On a positive note, the complex transition to a free market (Milošević and ĐorĐević 2015;Jucu 2016;Yaskal et al 2018) also boosted the development of businesses and employment in the services sector (Kunc et al 2014;Choromides 2017). However, the decline in manufacturing employment often proceeded much more rapidly than the creation of service jobs.…”
Section: Introductionmentioning
confidence: 99%